The role of social norms in practicing amr ma’ruf nahi munkar: A case study at Sabilurrasyad Pesantren - Handayani, Triana; Bakri, Maskuri; Hakim, Dian Mohammad (Abjadia : International Journal of Education, 2025)
This study explores the application of the concept of "khairu ummah" through non-formal education at the Sabilurrosyad Islamic Boarding School, Malang, with a focus on the role of religious traditions in shaping individual character. The background of this study is driven by the decline in morals and erroneous understanding of religion in Indonesia, which is evident in social events such as violence and religious conflict. This study uses a qualitative approach with case studies, involving observation, interviews, and documentation to analyze how religious traditions, such as congregational prayer and tadarus Al-Qur'an, contribute to the formation of khairu ummah character. The results of the study indicate that the application of religious traditions consistently and structured is effective in shaping individuals who meet the criteria of khairu ummah, which includes the integration of the values of amar ma'ruf nahi munkar and iman billah in everyday life. This study emphasizes the importance of expanding socialization and implementing the principle of khairu ummah to overcome the decline in morals and understanding of religion in society.